Effect of Earnings Per Share in Stock Return in the LQ 45 Period 2016 - 2022 - Krisnaldy (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine Earning Per Share on stock returns in LQ 45 for the 2016 – 2022 period, to determine the partial effect of Interest Rate on stock returns in LQ 45 companies for the 2016 – 2022 period, to determine the partial effect of Interest Rate on stock returns in LQ 45 companies for the period 2016 – 2022 and to determine the simultaneous effect of interest rates and exchange rates on stock returns in LQ 45 companies for the period 201 6 – 202 2 . The research method used in this research is multiple linear regression analysis. The data used in this study uses secondary data obtained from financial reports and data from Bank Indonesia. The selection of samples in this study are companies that are listed on the IDX from 20 16 to 202 2 which are included in the company. The results of the study stated that the variables partially had no effect on stock returns while the interest rate and exchange rates had a partial effect on stock returns. Simultaneously variables, Interest Rates, and exchange rates have a significant influence on stock returns. Based on the results of the coefficient of determination that the variable, Interest Rate and exchange rates have the greatest influence Interest Rate and exchange rates have a significant influence on stock returns. Based on the results of the coefficient of determination that the variable, Interest Rate and exchange rates have the greatest influence Interest Rate and exchange rates have a significant influence on stock returns. Based on the results of the coefficient of determination that the variable, Interest Rate, and exchange rates have the greatest influence 39.7%.